2016
DOI: 10.3390/ijerph13030279
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Temperature-Mortality Exposure-Response Relationships and Optimum Ambient Temperature at the Multi-City Level of China

Abstract: Few studies have explored temperature–mortality relationships in China, especially at the multi-large city level. This study was based on the data of seven typical, large Chinese cities to examine temperature-mortality relationships and optimum temperature of China. A generalized additive model (GAM) was applied to analyze the acute-effect of temperature on non-accidental mortality, and meta-analysis was used to merge data. Furthermore, the lagged effects of temperature up to 40 days on mortality and optimum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…We found that all causes of death could be significantly increased under exposure to high temperature, especially extremely high temperature. This result agrees with many previous findings for single outcomes, including non-accidental mortality (Guo et al, 2014; Zeng et al, 2016), circulatory disease (Anderson and Bell, 2009; Gasparrini et al, 2012; Huang et al, 2014), acute myocardial infarction (Gasparrini et al, 2012; Schwartz et al, 2004), coronary heart disease (Tian et al, 2012), stroke (Chen et al, 2013), and respiratory disease (Anderson and Bell, 2009; Gasparrini et al, 2012; Liu et al, 2011). All causes of deaths generally increase with increasing age, and populations of 75 years or older are associated with a larger heat effect, as reported in previous studies (Anderson and Bell, 2009; Gasparrini et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that all causes of death could be significantly increased under exposure to high temperature, especially extremely high temperature. This result agrees with many previous findings for single outcomes, including non-accidental mortality (Guo et al, 2014; Zeng et al, 2016), circulatory disease (Anderson and Bell, 2009; Gasparrini et al, 2012; Huang et al, 2014), acute myocardial infarction (Gasparrini et al, 2012; Schwartz et al, 2004), coronary heart disease (Tian et al, 2012), stroke (Chen et al, 2013), and respiratory disease (Anderson and Bell, 2009; Gasparrini et al, 2012; Liu et al, 2011). All causes of deaths generally increase with increasing age, and populations of 75 years or older are associated with a larger heat effect, as reported in previous studies (Anderson and Bell, 2009; Gasparrini et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The inclusion of 531,794 deaths provides high statistical power for our analysis and a more accurate description of heat-related effects. Compared to previous studies of multi-cities (Chen et al, 2013; Huang et al, 2015; Ma et al, 2014; Zeng et al, 2016) and global communities (Gasparrini et al, 2015; Guo et al, 2014), another strength of this study is our inclusion of non-accidental death and five different causes, which enables us to understand the responses of cause-specific diseases under exposure to high temperature and characteristics for different population groups. The findings have important public health implications for targeted disease control and prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations